(untitled) (Research, Society and Development, 2021)
The COVID-19 is an infectious disease caused by the SARS-CoV-2 virus, which belongs to the new strain of the coronavirus, identified in China in early December 2019. This one presents symptoms and serious conditions, which can lead to Severe Acute Respiratory Syndrome. Thus, the need for a laboratory hematological profile of SARS-CoV-2 infection and its monitoring, becomes of great value to assist in the prognosis and treatment of the disease. This systematic review aims to trace the hematological profile resulting from infection by the SARS-CoV-2 virus, identifying the main changes found in the leukogram, erythrogram and platelet chart. For the elaboration of this study, an electronic search was carried out in several databases. The most frequently found hematological changes were lymphopenia, leukopenia, neutrophilia associated with leukocytosis, eosinopenia, reduced hemoglobin, thrombocytopenia and platelet aggregation, in addition to morphological changes. Anemia was not noticeably observed, but the reduction in hemoglobin was evident in healthy patients. The coagulation factors associated with platelet reduction as well as its hyper activation were altered in critically ill patients. These changes demonstrate the state of hypercoagulability present in critically ill patients with COVID-19, present in microthrombus pictures in various organs, being one of the most serious complications of COVID-19. Therefore, platelet count and changes in parameters associated with platelets are currently a concern. However, with the survey carried out, it is evident that an inflammation associated with high oxidative damage will compromise the hemostasis and leukocyte physiology of patients with COVID-19.